Development, Implementation, And Evaluation of An Informatics Platform for Home Based Self- Management of Chronic Obstructive Pulmonary Disease: A Study Protocol - Verma, Ashwani; Behera, Ashok; Islam, KM Monirul; Joshi, Ashish (National Journal of Community Medicine, 2023)
Background: The burden of chronic obstructive pulmonary disease to patients, their caretakers, and health system is gradually increasing and is associated with the morbidity, mortality, disability adjusted life years and higher costs. Self-management of COPD is a vital strategy for its management. This study aims to develop, implement, and evaluate an informatics platform for the home-based self-management of Chronic Obstructive Pulmonary Disease. Method: A systematic review will be conducted to synthesize and appraise the evidence on self-management informatics tool or platform for COPD. An evidence-based COPD self-management application will be developed and implemented to 35 COPD patients at identified hospitals of New Delhi using prospective non-randomized study. A mixed methods study will be conducted to evaluate the effectiveness of this informatics platform at selected hospitals of Delhi. Outcomes will be measured in terms of self-management for COPD related exacerbations, number of health care facility admissions for COPD and hospitalization days, adherence to the informatics platform, number of exacerbations requiring hospital visits, health related quality of life. Conclusion: The development and evaluation of home-based self-management of informatics platform for COPD would be an innovative strategy for the COPD patients in India.